Perspectives from Supplemental Nutrition Assistance Program Participants on Improving SNAP Policy - Cindy W. Leung; Julia A. Wolfson (Mary Ann Liebert, 2019)
Purpose: Supplemental Nutrition Assistance Program (SNAP) participants are important stakeholders in improving program policies, but their voices have not been included in the public discourse. Methods: We assessed the opinions of 202 SNAP participants and 368 food-insufficient nonparticipants on proposed SNAP policies. Results: The majority of SNAP participants and nonparticipants supported increasing federal SNAP spending, policies to broaden the usage of SNAP benefits, and policies to improve the healthfulness of foods purchased with SNAP benefits. However, 60% opposed the America's Harvest Box proposal. Conclusion: The perspectives of SNAP participants on restructuring the program's reach or nutritional impact should be considered.